Ganoderma Lucidum Polysaccharides Enhance the Abscopal Effect of Photothermal Therapy in Hepatoma-Bearing Mice Through Immunomodulatory, Anti-Proliferative, Pro-Apoptotic and Anti-Angiogenic - Xia, Qing-Hai; Lu, Cui-Tao; Tong, Meng-Qi; Yue, Meng; Chen, Rui; Zhuge, De-Li; Yao, Qing; Xu, He-Lin; Zhao, Ying-Zheng (Frontiers in Pharmacology, 2021)
Hepatocellular carcinoma is a malignant tumor with high morbidity and mortality, a highly effective treatment with low side effects and tolerance is needed. Photothermal immunotherapy is a promising treatment combining photothermal therapy (PTT) and immunotherapy. PTT induces the release of tumor-associated antigens by ablating tumor and Ganoderma lucidum polysaccharides (GLP) enhance the antitumor immunity. Results showed that ICG was successfully encapsulated into SF-Gel. ICG could convert light to heat and SF-Gel accelerates the photothermal effect in vitro and in vivo. PTT based on ICG/ICG-SF-Gel inhibited the growth of primary and distal tumors, GLP enhanced the inhibitory efficacy. ICG/ICG-SF-Gel-based PTT and GLP immunotherapy improved the survival time. ICG/ICG-SF-Gel-based PTT induces tumor necrosis and GLP enhanced the photothermal efficacy. ICG/ICG-SF-Gel-based PTT inhibited cell proliferation and angiogenesis, induced cell apoptosis, enhanced cellular immunity, and GLP enhanced these effects. In conclusion, GLP could enhance the abscopal effect of PTT in Hepatoma-bearing mice.